Statistics - Abadir, Karim M., 1964-; Heijmans, Risto D. H.; Magnus, Jan R. (Cambridge : Cambridge University Press, 2019)
Building on the success of Abadir and Magnus' Matrix Algebra in the Econometric Exercises Series, Statistics serves as a bridge between elementary and specialized statistics. Professors Abadir, Heijmans, and Magnus freely use matrix algebra to cover intermediate to advanced material. Each chapter contains a general introduction, followed by a series of connected exercises which build up knowledge systematically. The characteristic feature of the book (and indeed the series) is that all exercises are fully solved. The authors present many new proofs of established results, along with new results, often involving shortcuts that resort to statistical conditioning arguments.
Machine generated contents note: Part I. Probability and Distribution Theory: 1. Probability; 2. Random variables, probability distributions and densities; 3. Expectations and their generating functions; 4. Special univariate distributions; 5. Joint distributions and densities; 6. Conditioning, dependence, and joint moments; 7. Functions of random variables; 8. The multivariate normal and functions thereof; Part II. Estimation and Inference: 9. Sample statistics and their distributions; 10. Asymptotic theory; 11. Principles of point estimation; 12. Likelihood, information, and maximum likelihood estimation; 13. Other methods of estimation; 14. Tests of hypotheses; Appendix A; Appendix B; Bibliography; Index.
Title from publisher's bibliographic system (viewed on 11 Jun 2020).
Keywords: elektronické knihy; electronic books; Econometrics; Mathematical statistics